Some insights on the clause linker -teh of Sakhalin Ainu through a consideration of aspect - Elia Dal Corso (Brill, 2022)
This paper attempts to advance the investigation on clause linkers of Sakhalin Ainu, which are a vastly under-studied topic of Ainu grammar. In this paper I focus on the linker -teh and, more precisely, I will take into account the two semantically analogous aspectual constructions V+-teh ‘an and V+‘an to show how the linker -teh (or lack thereof) contributes to their, in fact, different functions. While I try to deepen our understanding of the SA aspectual system by looking at the two above-mentioned constructions and arguing for their status as markers of (im)perfectivity, I will eventually propose the analysis of -teh as a subordinate linker.